Potensi Pengembangan Tanaman Hijauan Indigofera Sebagai Pakan Ternak Di Desa Karanggatak Kabupaten Boyolali - Anisa Rahmawati Solikah; Luki Abdullah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Feed is the most important factor in livestock business. The problem often faced in the livestock business is the supply of forage materials. This study aims to determine the potential of indigofera forage plants as animal feed in Desa Karanggatak, Kecamatan Klego, Kabupaten Boyolali. The results showed that Indigofera sp. has a high nutritional content. Indigofera sp. can survive in dry and extreme land. Indigofera sp. potential to be developed as feed in Desa Karanggatak. Keywords : Animal Forage, Indigofera, Animal Feed